Feasibility of Soil and Water Conservation Techniques on Oil Palm Plantation - Murtilaksono, Kukuh; Darmosarkoro, Witjaksana; Sutarta, Eddy Sigit; Siregar, Hasril Hasan; Hidayat, Yayat; Yusuf, M. Arif (AGRIVITA, Journal of Agricultural Science, 2011)
The objective of the study is to examine the effectiveness and feasibility of soil and water conservation techniques. The production of oil palm comprising the fresh fruit bunch, number of bunches, and average of bunch weight were recorded at every harvesting schedule. Tabular data were analyzed by logical comparison among the blocks as a result of application of bund terraces and silt-pit. Financial and sensitivity analysis of the effect of the techniques on FFB production were done. Bund terrace treatment was more effective (4.761 ton or 21.5%) in increasing FFB production than the silt-pit treatment (3.046 ton or 13.4%) when it is compared to that of the control block. The application of bund terraces and silt-pit also presents positive effects i.e. increases the average bunch weight and the number of bunch compared to that of the control. Furthermore, the financial analysis as well as sensitivity analysis shows that the bund terrace application is profitable and feasible (B/C = 3.06, IRR = 47%) while the silt pit treatment is profitable but not feasible.Keywords: Bund terrace, feasibility, production of FFB, silt-pit